Financial cycles: What are they and what do they look like in Denmark? - Oliver Juhler Grinderslev; Paul Lassenius Kramp; Anders Farver Kronborg; Jesper Pedersen (Danmarks Nationalbank, 2017)
Financial cycles have received a lot of attentions since the financial crises. In this paper we study what financial cycles are, what they look like in Denmark, and what their relationship is with the real economy. We show that medium term swings in house prices and credit should be used as an illustration of the financial cycle in Denmark. There are, however, difficulties in detecting financial cycles in real time. Across countries and in Denmark, there are strong co-movements in house prices, credit and GDP at both business and medium term frequencies (11-30 years), i.e. financial cycles are strongly connected with the real economy. Peaks in the financial cycle have in fact historically been predictors of financial crises. The financial cycle can therefore be used an indicator when monitoring risks that can materialize into financial stress. – – Efter den finansielle krise er der kommet øget fokus på finansielle cykler. I dette arbejdspapir undersøger vi, hvad finansielle cykler er, hvordan de ser ud i Danmark, og hvad sammenhængen er mellem dem og realøkonomien. Vi viser, at mellemlange udsving i huspriser og kredit kan anvendes til at illustrere den finansielle cykel i Danmark. Der er dog udfordringer med at bestemme finansielle cykler i realtid. På tværs af lande og i Danmark er der stærk samvariation mellem huspriser, kredit og BNP både på konjunktur og mellemlange (11-30 år) frekvenser. Det betyder, at finansielle cykler er stærkt forbundne med realøkonomien. Toppunkter i den finansielle cykel har ofte været sammenfaldende med finansielle kriser. Finansielle cykler kan derfor bruges som en indikator i forbindelse med overvågning af risici, som kan føre til finansiel stress.
Keywords: 330